The Determinants of Sustainable Apparel Products In Indonesia Exploring Consumer “Attitude-Purchase Intention” Gap - Fitriatul Zahroh (PT. Publikasiku Academic Solution, 2023)
Fashion products have a short cycle that results in harmful environmental damage, a shift to more sustainable consumption purchase is needed in Indonesia. Although public interest in sustainability has increased and consumer attitudes are positive, their purchase intentions are inconsistent with attitudes. This study aims to reveal the psychological drivers and barriers (utilitarian consumption, social norms, attitudes) as well as the price-saving orientation of Indonesian consumers' purchase intentions towards thrifting clothing products by exploring the attitude-purchase intention gap. Online survey data were used to examine the moderate impact of utilitarian consumption, social norms and price-saving orientations on the relationship between Indonesian consumers' attitudes and purchase intentions towards thrifting products, particularly the greater Jakarta area. The results of the PLS-SEM analysis show that (1) attitude has a significant influence on purchase intention, (2) utility value negatively moderated the relationship, (3) and social norms negatively moderated the relationship, (4) while price saving orientation has a positive relationship to purchase intention. This study does not validate the attitude-purchase gap model in sustainable consumer purchase, however it does discuss how the current findings can help researchers and practitioners in the Apparel and Textile field to refine and improve sustainable programs and marketing strategies in Indonesia.